1997
DOI: 10.3109/01050399709048010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Severely and Profoundly Hearing-Impaired Children's Amplification Preferences with the NAL-RP and the DSL 3.0 Prescriptions

Abstract: Prompted by a recent paper in this journal (Snik et al., 1995), this communication compares the gain and frequency response preferred by a group of 21 severely and profoundly hearing-impaired children (37 test ears) to the NAL-RP and the DSL 3.0 hearing aid prescriptions. The results support the findings of Snik et al. (1995) that the NAL-RP procedure provides an adequate prescription of amplification on average. The individual discrepancies between prescribed and preferred characteristics imply that fine-tuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…Presumably, the children in Canada were accustomed to using higher gains associated with DSL, and may therefore have been able to use it more successfully than the children in Australia. This fi nding is consistent with the discrepancy between the Ching et al (1997) and Scollie et al (2000) studies, in which Australian and Canadian children preferred NAL and DSL, respectively. These previous studies did not employ blinding in their designs, making it diffi cult to determine whether children's previous use histories, lack of acclimatization, or experimenter biases were responsible for the discrepancies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Presumably, the children in Canada were accustomed to using higher gains associated with DSL, and may therefore have been able to use it more successfully than the children in Australia. This fi nding is consistent with the discrepancy between the Ching et al (1997) and Scollie et al (2000) studies, in which Australian and Canadian children preferred NAL and DSL, respectively. These previous studies did not employ blinding in their designs, making it diffi cult to determine whether children's previous use histories, lack of acclimatization, or experimenter biases were responsible for the discrepancies.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of children's preference (i.e. Ching et al, 1997;Scollie et al, 2000) have been conducted in controlled listening environments at a single test level. Clearly, the children's comments elicited in this study indicate that they are faced with a very wide range of acoustic environments, many of which are not represented well by a laboratory test of preference.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These level-dependent effects are consis tent with the auditory system changing in its responsiveness to levels that were not frequently encountered prior to hearing-aid use. The signifi cant loudness acclimatization effects observed here may help to explain discrepancies in preferred listening levels reported in earlier studies of children accustomed to using either DSL or NAL (Ching et al, 1997;Scollie et al, 2000). That is, the prior use histories of the children in these studies may have affected the loudness, biasing the preference judgements in favour of a fi tting that provided loudness that was similar to that used in the children's own hearing aids.…”
Section: Effects Of Experiencementioning
confidence: 70%
“…On average, the preferred gain averaged across 0.5, 1, and 2 kHz (3FA) was not signifi cantly different from that prescribed by DSL v4.1, but was signifi cantly higher than the NAL-RP/NAL-NL1 prescriptions (the NAL prescription for linear and non-linear hearing aids respectively). On the other hand, Ching et al (1997Ching et al ( , 1999 showed that the required 3FA gain of 43 severely or profoundly hearing-impaired children (71 ears; mean 3FA hearing threshold level (HTL) = 95 dB HL) for listening to speech at 65 dB SPL at a comfortable level was not signifi cantly different from the NAL-RP target gains.…”
Section: Sumariomentioning
confidence: 96%